AI Integration to Improve Teachers’ Efficiency in Developing Instructional Media - Aryo Baskoro Utomo; Sita Nurmasitah; Adhi Kusumastuti; Wulansari Prasetyaningtyas; Pudji Astuti; Ismanto Ismanto; Dimas Afrianto; Naura Atika Cahya Anggrayni; Annafie Aina Nabilla; Cellomita Salsabila (Universitas Negeri Semarang, 2025)
Although Artificial Intelligence (AI) has been widely explored in higher education, research on its integration in elementary teacher training remains limited, particularly in developing contexts. This study investigates whether AI-based training can enhance teachers’ efficiency in developing instructional media. A quasi-experimental design with a one-group pre-test–post-test approach was employed. Twenty elementary school teachers from Indonesia participated in a four-week training program involving lectures, guided practice, and mentoring on AI platforms such as ChatGPT, QuillBot, Canva AI, and Quizizz AI. Data were collected through pre-test and post-test assessments (15 multiple-choice items) and a perception questionnaire using a five-point Likert scale. Results showed a significant increase in teachers’ understanding, with mean scores rising from 55.6 to 86.1, indicating a 30.5-point improvement. Teachers also reported high satisfaction with the training (M = 4.76/5), especially regarding efficiency and applicability in classroom practice. These findings suggest that short-term AI-based professional development can reduce teachers’ workload, strengthen digital literacy, and support sustainable educational innovation. The study contributes to global discussions on leveraging AI for teacher capacity building, particularly in resource-constrained elementary education systems.